The Erosion of the Country of Origin Effect: A Case Study of a Swedish Multinational Company - Hayden, Annette; Edwards, Tony (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles, 2001)
SummaryOver the last two decades, Swedish capital has undergone a rapid internationalization. This has presented a significant challenge to the distinctive nature of the Swedish economy in general and its employment relations system in particular. A key question arising is: to what extent, and in what ways, are Swedish multinationals influenced by the distinctiveness of the country of origin in the way they manage their international workforces? We investigate these issues through examination of data gathered from a mini-case study of a large Swedish multinational. We show how the firm has adopted practices experienced in its foreign operations and deployed these throughout the corporation. This process has eroded, though not removed, the influence of the Swedish system on employment relations in the multinational, with the British and American systems appearing to exert a growing influence. We explain the findings with reference to managerial perceptions of the strengths and weaknesses of different “national business systems.”